IMPLEMENTATION OF SOCIAL STUDIES TEACHERS' WORKING MEETING (MGMP) IN IMPROVING TEACHER PERFORMANCE IN JUNIOR HIGH SCHOOLS IN SOUTHWEST ACEH DISTRICT - Lizmi; Ismail; Nasir Usman (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This punishment is included in the nomination for the Social Sciences Professional Teacher Competency Award for the personality and effectiveness of social studies leaders in schools. And for many MGMP IPS awards for Eastern Aceh Province as an extraordinary energy teacher. This research mentions qualitative performance. Data collection techniques are discussed carefully, observation and documentation. The subjects in this research were MGMP administrators, MGMP members, and school principals. These achievements are listed below: 1) developing a program strategy by developing the vision and success of the program, creating a structure that supports the program, developing program themes, and getting coordination with successful outreach or through social media, 2) Yesterday's MGMP program was less than two day at school in Southwest Aceh province and one until but that was two months ago at the end of the day by the head of the MGMP, maintenance school, and main school, with a high temperature. According to the little-known MGMP penguin organization, the body time base of penguins in MGMP projects needs to be evaluated based on various internal and external factors that contribute to the MGMP IPS project. Yesterday, the Governor of North East Aceh's MGMP IPS was also effectively considered a kinetic teacher.